A Study To Examine The Factors Driving Tamasha Folk Theatre's Influence On India's Classical Theatre (Journal of Namibian Studies : History Politics Culture, 2023)
The conventional Tamasha has likewise receded and relinquished its position in the consciousness of the devoted audience. Amasha, a dynamic folk theater tradition renowned for its energetic song, dance, and emotive narrative, has successfully infiltrated India's classical theatre, resulting in a fusion of styles and methods. This research conducts a thorough analysis to investigate the ways in which cultural interaction, regional influences, and audience preference for newness have enabled the incorporation of Tamasha components into classical compositions. Tamasha's rhythmic music, energetic dance forms, and humorous storylines have had a significant effect on traditional theater by bringing in new and captivating techniques. The research enhances our comprehension of the development of Indian theater and its rich creative legacy by revealing the variables that lead to this synthesis. It also provides valuable insights into the continuous blending of traditional and modern performance forms.